Multitouch-based collaborative pre-visualisation for computer animation - Lwabona, Kwegyir (Bilo) (Department of Computer Science, 2016)
Computer animated pre-visualisation occurs at an early stage of visualising scenes in low-fidelity. This is a collaborative process, in which directors communicate with animators how shot sequences will occur. Producers also take notes to approximate costs and other stakeholders may give further input. The problem with this approach is that the improvement cycles can take a long time, making the process take exponentially longer with more iterations of improvement. Our aim is to create a system that reduces this time, while keeping every stakeholder of the animation on the same page. We have constructed a multitouch-enabled system for low-fidelity, animated 3D pre-visualisation. This tool runs on a single, large multitouch table and caters for simultaneous input from multiple users, to better support collaboration. Users can navigate the virtual environment, place and manipulate 3d objects in the scene, as well as animate them, all using multitouch. The system was constructed using the user-centred systems design (UCSD) methodology. After several iterations of development, we performed a qualitative evaluation of the _nal system using two groups, one consisting of film makers and the other consisting of software developers, and concluded with interviews to get qualitative feedback about our pre-visualisation tool. Both groups suggested that the system's setup promoted collaboration and communication, which is important early on in the planning phase of film creation. However, both groups agreed that such a tool is only useful for low-fidelity pre-visualisation, as it might become "cumbersome" to perform detailed animations using multitouch input. Furthermore, the system was often too dependent on the viewpoint, which was a single user task, effectively minimizing the amount of work that could actually be done by collaborative users simultaneously. This study highlights the potential of a multitouch, collaborative pre-visualisation tool.